Physical Activity Among Unimas Undergraduates - Jeffery, Stephen; Rafidah, Elias; Beatrice Reen, Gilbert; Nurul Adilah, Mohamed Farid; Tong, Desmond Ming Han; Sarah Prosper, Atang (IJCRR, 2021)
Background: A significant decline in physical activity is seen among young adults during the transition into adulthood. Objective: This study aims to explore the degree of physical activity among undergraduate students in University Malaysia Sarawak (UNIMAS) and its relationship with five predictors for behavioural change related to participation in physical activity, derived from Health Promotion Model. Methods: This cross-sectional study was conducted among 440 undergraduate students through multistage random sampling using self-administered questionnaire consists of Global Physical Activity Questionnaire (GPAQ), Exercise Benefit/Barrier Scale (EBBS), Self-rated Abilities for Health Practices Scale (SRAHP), Physical Activity Affect Scale (PAAS) and Physical Activity and Social Support Scale (PASSS). Results: From 409 respondents, 74.1% was physically active. Mean age of physically active was 21 years old, Year-2 students (31.3%) more active than Year-1 (30.8%) and Year-3 (12%), and females (48.7%) than males (25.4%). Males were three times more prone to participate in physical activity than females (OR=3.533). Predictors, namely perceived benefit, perceived barrier, and self-rated ability had a significant relationship with the degree of physical activity, in contrast with social influence and activity-related effect. Conclusion: Majority were physically active. Only self-rated ability likely to predict a student’s participation in physical activity.